2009
DOI: 10.1212/01.wnl.0000341934.12142.74
|View full text |Cite
|
Sign up to set email alerts
|

Results of the Avonex Combination Trial (ACT) in relapsing-remitting MS

Abstract: This trial did not demonstrate benefit of adding low-dose oral methotrexate or every other month IV methylprednisolone to interferon beta-1a in relapsing-remitting multiple sclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(31 citation statements)
references
References 21 publications
(22 reference statements)
0
31
0
Order By: Relevance
“…The primary endpoint of new or enlarged T2 lesions comparing baseline and 12 month MRI scan was not met for any group. Nonsignificant trends in secondary outcomes variably favored either MTX or IVMP [56].…”
Section: Combination Trialsmentioning
confidence: 97%
“…The primary endpoint of new or enlarged T2 lesions comparing baseline and 12 month MRI scan was not met for any group. Nonsignificant trends in secondary outcomes variably favored either MTX or IVMP [56].…”
Section: Combination Trialsmentioning
confidence: 97%
“…However, because of slow patient recruitment, the study was redesigned with a smaller enrollment target and shorter duration of follow up. In the redesigned study, 313 eligible patients entered the study on stable doses of IM IFNb-1a (30 mg once weekly) and were randomized to a 12-month course of adjunctive therapy with placebo (group 1), oral methotrexate 20 mg once weekly (group 2), intravenous methylprednisolone 1000 mg/day for 3 consecutive days every other month (group 3), or oral methotrexate and intravenous methylprednisolone at the same doses as in groups 2 and 3 (group 4) [Cohen et al 2009]. The primary endpoint was new or enlarged T2-hyperintense lesions, and secondary endpoints were EDSS scores, Multiple Sclerosis Functional Composite (MSFC) scores, and relapses.…”
Section: Combination Therapy With Ifnbmentioning
confidence: 99%
“…Such findings point to inconclusive evidence of efficacy in PRMS, and there are no sufficiently welldesigned trials to ascertain the effectiveness of methotrexate monotherapy in RRMS. More recently, the randomized Avonex Combination Trial (ACT), which included 313 patients with RRMS, found no significant benefit of adding low-dose methotrexate to treatment in patients with ongoing disease activity while receiving IFNb-1a monotherapy [Cohen et al 2009]. Taken together, these findings suggest that methotrexate is likely to have only a limited role in MS management and therefore should not be used as a substitute for currently approved therapies.…”
Section: Cyclophosphamidementioning
confidence: 99%